2019
DOI: 10.1002/tea.21614
|View full text |Cite
|
Sign up to set email alerts
|

Mapping undergraduate chemistry students' epistemic ideas about models and modeling

Abstract: Developing and using scientific models is an important scientific practice for science students. Undergraduate chemistry curricula are often centered on established disciplinary models, and assessments typically provide students with opportunities to use these models to predict and explain chemical phenomena. However, traditional curricula generally provide few opportunities for students to consider the epistemic nature of models and the process of modeling. To gain a sense of how introductory chemistry studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 76 publications
(192 reference statements)
0
36
0
Order By: Relevance
“…Table 1 summarizes various forms of epistemic uncertainty in different phases of modeling, and it also notes what epistemic knowledge can be used for productive leveraging of epistemic uncertainty that leads to knowledge development. In constructing Table 1, I considered the scholarship conceptualizing epistemic knowledge, epistemic uncertainty, and the practice of modeling in learning science (e.g., Campbell & Fazio, 2020;Chen & Qiao, 2020;Lazenby et al, 2020;Lee et al, 2014;Metz, 2004;Oliva & Blanco-L opez, 2021). It is important to understand that this framework does not reflect a linear process, even if represented in a linear manner.…”
Section: Theoretical Framework: Variation Of Epistemic Uncertainty Drives Modeling In Its Different Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes various forms of epistemic uncertainty in different phases of modeling, and it also notes what epistemic knowledge can be used for productive leveraging of epistemic uncertainty that leads to knowledge development. In constructing Table 1, I considered the scholarship conceptualizing epistemic knowledge, epistemic uncertainty, and the practice of modeling in learning science (e.g., Campbell & Fazio, 2020;Chen & Qiao, 2020;Lazenby et al, 2020;Lee et al, 2014;Metz, 2004;Oliva & Blanco-L opez, 2021). It is important to understand that this framework does not reflect a linear process, even if represented in a linear manner.…”
Section: Theoretical Framework: Variation Of Epistemic Uncertainty Drives Modeling In Its Different Phasesmentioning
confidence: 99%
“…Modeling, however, has often been presented such that the student receives a final form of science knowledge (Lazenby et al, 2020;Lehrer, 2009;Manz et al, 2020). For example, when learning about Gay Lussac's law (i.e., the relationship between the pressure and the absolute temperature of ideal gas), traditional teachers may directly introduce the equation and model developed by scientists, and ask students to remember and use the equation to calculate problems.…”
Section: Introductionmentioning
confidence: 99%
“…Another issue to consider is that some authors have criticized the fact that the vast majority of research on epistemic beliefs has used self‐report surveys (Lindfors et al, 2020). It is argued that this type of instrument, particularly when consisting of closed items, may allow students to give “high‐level” answers based on hearsay only (Sins et al, 2009), whereas qualitative studies suggest that students in fact have a naïve and unsophisticated epistemological understanding of models (Lazenby et al, 2019). However, although it is true that closed questionnaires, such as Likert‐type scales, may produce an inflated view of students' epistemic knowledge, it is also possible that a student does have adequate knowledge in this respect but is unable to demonstrate it when answering an open written question (Lazenby et al, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It is argued that this type of instrument, particularly when consisting of closed items, may allow students to give “high‐level” answers based on hearsay only (Sins et al, 2009), whereas qualitative studies suggest that students in fact have a naïve and unsophisticated epistemological understanding of models (Lazenby et al, 2019). However, although it is true that closed questionnaires, such as Likert‐type scales, may produce an inflated view of students' epistemic knowledge, it is also possible that a student does have adequate knowledge in this respect but is unable to demonstrate it when answering an open written question (Lazenby et al, 2019). Consequently, we should perhaps consider that any instrument, regardless of its format, is only of value for making assessments in relative—as opposed to absolute—terms.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It suggests that students need to develop and employ their metacognition and epistemic knowledge of visualization for successful visualization. Separate studies have indicated the importance of metacognition (Bennett et al, 2020) and epistemic knowledge about models and modeling (Lazenby et al, 2020; Schwarz & White, 2005) for the whole process of model‐based learning, such as building and using models to generate scientific explanations. Applying the notion of metavisualization allows the focus only on the visualization construction part, but with a more holistic lens inclusive of both metacognition and epistemology to investigate how the two play a role in supporting students’ successful visualization.…”
Section: Introductionmentioning
confidence: 99%